2023
DOI: 10.1002/ehf2.14399
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin peptides and precursor levels in relation to haemodynamics and prognosis after heart transplantation

Abstract: Aims Heart failure (HF) is a frequent condition in the elderly, further complicated by associated pulmonary hypertension (PH), with impact on morbidity and mortality. Plasma proteins associated with cardiovascular disease, related to inflammation, neurohormonal changes, and myocyte stress, pathways recognized in the pathophysiology of HF, may provide information on disease severity and prognosis. We aimed to investigate such cardiovascular proteins and their relationship to haemodynamics before and 1 year afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…10 Additionally, it is strongly associated with pulmonary capillary wedge pressure, right atrial pressure, N-terminal pro-B-type natriuretic peptide (NT-proBNP) and elevated pre-discharge bio-ADM is strongly associated with HF rehospitalizations. [10][11][12] Optimal treatment to relieve congestion is currently under discussion. 8,13 Although decongestion with loop diuretics remains the first choice during the early phases of a HF hospitalization, data from STRONG-HF have shown that early initiation and fast up-titration of GDMT not only reduces congestion but improves clinical outcomes as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Additionally, it is strongly associated with pulmonary capillary wedge pressure, right atrial pressure, N-terminal pro-B-type natriuretic peptide (NT-proBNP) and elevated pre-discharge bio-ADM is strongly associated with HF rehospitalizations. [10][11][12] Optimal treatment to relieve congestion is currently under discussion. 8,13 Although decongestion with loop diuretics remains the first choice during the early phases of a HF hospitalization, data from STRONG-HF have shown that early initiation and fast up-titration of GDMT not only reduces congestion but improves clinical outcomes as well.…”
Section: Introductionmentioning
confidence: 99%
“…Bio‐ADM is a promising marker for residual congestion 10 . Additionally, it is strongly associated with pulmonary capillary wedge pressure, right atrial pressure, N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and elevated pre‐discharge bio‐ADM is strongly associated with HF rehospitalizations 10–12 …”
Section: Introductionmentioning
confidence: 99%